PENGGUNAAN CENDAWAN ENTOMOPATOGEN Beauveria bassiana (BALSAMO) VUILLEMIN DAN Lecanicillium lecanii (ZIMM) ZARE & GAMS UNTUK MENGENDALIKAN Helopeltis antonii SIGN (HEMIPTERA: MIRIDAE) The Use of Entomopathogenic Fungi Beauveria bassiana (Balsamo)Vuillemin - Sri Hastuti Anggarawati; Teguh Santoso; Ruly Anwar (Jurnal Silvikultur Tropika, 2017)
Helopeltis sp. has been known as one of major pests on tea, cacao and cashew plantation. Recently, genus Helopeltis is also reported attack Acacia plantation in Sumatra and Kalimantan. For such extensive plantation, low cost biocontrol agents like entomopathogenic fungi are choosen because of the simplicity for mass production. The objective of this study was to measure the effectiveness of Beauveria bassiana and Lecanicillium lecanii against Helopeltis sp. Both fungi that were used in this study were obtained from IPB Insect Pathology Laboratory. The tested insect, Helopeltis sp. was collected from Gunung Mas tea plantation. The insects were reared in laboratory. Four level of conidial density, 109, 108, 107, 106 conidia/ mL were applied to Helopeltis adult (B. bassiana) and 3rdinstar nymph (L. lecanii). Daily mortality was observed until seven days post treatment. The result showed that L. lecanii at 106 conidia/mL caused 96.25% mortality of 3rd instar nymph of Helopeltis sp. with the LC50 value at two days observation was 1.03 x 106 conidia/ mL, LT50 was 1.198 days and LT95 was 5.25 days. On the other hand, B. bassiana at 106 conidia/ mL caused 81.25%. mortality of adult Helopeltis sp. while 100% mortality could be attained by using 108 conidia/ mL. The LC50 of B. bassiana was 3.2 x 104 conidia/ mL, at four days observation and LT50 was 4.214 days. The two fungi were thus judged effective against Helopeltis sp. in this bio assay.Key words: Beauveria bassiana, conidia, density, Helopeltis sp., Lecanicillium lecanii, mortality.